2014
DOI: 10.17221/425/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of root respiration to soil respiration in a rape (Brassica campestris L.) field in Southwest China

Abstract: This study aimed to separate the respective contributions of root and microbial respiration to soil respiration in a rape field in Southwest China. The soil respiration was measured with a closed chamber technique and a regression method was used to apportion root and microbial respiration. Microbial and root respiration ranged from 70.67 to 183.77 mg CO 2 /m 2 /h and 21.99 to 193.09 mg CO 2 /m 2 /h, averaged 127.16 and 116.66 mg CO 2 /m 2 /h during the rape growing season, respectively. Root respiration coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Relationship between the soil respiration and plant biomasses were not noticeable in this study owing to limitations of continuously measured biomasses of the grassland throughout the year, and especially in the plants growing season. [96]. According to Geng et al [95], the variation in soil respiration with below-ground biomass was attributed at 80% among different sites, and below-ground biomass was directly correlated with root respiration of 31% -51% in C3/C4 grassland [97], 14.5% -62.62 % in rape field [96], 33% -71% in perennial grassland [14] which is the major contributor of soil respiration in grassland.…”
Section: Soil Respiration and Plant Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between the soil respiration and plant biomasses were not noticeable in this study owing to limitations of continuously measured biomasses of the grassland throughout the year, and especially in the plants growing season. [96]. According to Geng et al [95], the variation in soil respiration with below-ground biomass was attributed at 80% among different sites, and below-ground biomass was directly correlated with root respiration of 31% -51% in C3/C4 grassland [97], 14.5% -62.62 % in rape field [96], 33% -71% in perennial grassland [14] which is the major contributor of soil respiration in grassland.…”
Section: Soil Respiration and Plant Biomassmentioning
confidence: 99%
“…[96]. According to Geng et al [95], the variation in soil respiration with below-ground biomass was attributed at 80% among different sites, and below-ground biomass was directly correlated with root respiration of 31% -51% in C3/C4 grassland [97], 14.5% -62.62 % in rape field [96], 33% -71% in perennial grassland [14] which is the major contributor of soil respiration in grassland. Limitations of research fund and the remoteness of the study area made it difficult to establish animal exclusion to measure the plant biomass and soil respiration with short measurement intervals throughout the year.…”
Section: Soil Respiration and Plant Biomassmentioning
confidence: 99%
“…Soil respiration components are usually separated into: (i) respiration from roots, exudates, mycorrhizae and microorganisms in obligate associations [autotrophic respiration (Ra)]; and (ii) respiration from soil microorganisms that subsist on the decomposition of soil organic matter [heterotrophic respiration (Rh)] (Scott‐Denton et al ). The spatial and temporal fluctuations in both components have been widely studied in grasslands (Baggs , Kuzyakov ), forests (Davidson et al ) and several crops (Buwalda , Hao and Jiang ). Conversely, few studies have focused on soil and root respiration of grapevines (Franck et al , Lardo et al ).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies paid relatively little attention to Rr/Rt ratio during non-growing season. Although the soil temperature, microbial activity and root biomass during non-growing season were obviously lower than growing season (Hao and Jiang 2014;Li et al 2018), and even the microbial activity was negligible in frozen soils (Wang et al 2009), the contribution of soil respiration to the total annual soil respiration was approximately 12% and the Rr/Rt ratio varied from 13% to 50% (Schindlbacher et al 2007). Thus, the root respiration during non-growing season also is a significant component of annual carbon budgets.…”
Section: Introductionmentioning
confidence: 96%
“…Li et al (2018) reported that the average Rr/Rt ratios were 41.7% and 41.9% for the growing season in 2008 and 2009 in the semi-arid grassland of northern China. Hao and Jiang (2014) found the Rr/Rt ratio averaged 44.2% in a rape (Brassica campestris L.) eld in Southwest China.…”
Section: Introductionmentioning
confidence: 97%